Physics without Metaphysics - Chackalackal, Saju (Journal of Dharma, 2005)
Raphael Neelamkavil, Physics without Metaphysics? Bangalore: Dharmaram Publications, 2006, pages xxvi + 382, ISBN: 8186861-89-0.